2016
DOI: 10.1371/journal.pone.0154405
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Exercise Attenuates Lipopolysaccharide-Induced Inflammation and Associated Maternal and Fetal Morbidities in Pregnant Rats

Abstract: Fetal growth restriction (FGR) and coagulopathies are often associated with aberrant maternal inflammation. Moderate-intensity exercise during pregnancy has been shown to increase utero-placental blood flow and to enhance fetal nutrition as well as fetal and placental growth. Furthermore, exercise is known to reduce inflammation. To evaluate the effect of moderate-intensity exercise on inflammation associated with the development of maternal coagulopathies and FGR, Wistar rats were subjected to an exercise reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…There are several immune-protective components in human milk, including cytokines (Field, 2005; Goldman, Chheda, Garofalo, & Schmalstieg, 1996), that could affect the development and immunologic function of the neonate (Goldman et al, 1996). In this sense, maternal inflammation could be down-regulated by exercise during pregnancy (Kasawara et al, 2016; Tinius et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several immune-protective components in human milk, including cytokines (Field, 2005; Goldman, Chheda, Garofalo, & Schmalstieg, 1996), that could affect the development and immunologic function of the neonate (Goldman et al, 1996). In this sense, maternal inflammation could be down-regulated by exercise during pregnancy (Kasawara et al, 2016; Tinius et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, regular and moderate exercise might be a powerful intervention for reducing subclinical inflammation (Volpe et al, 2007). Moreover, it may in turn decrease the severity of maternal and perinatal complications associated with abnormal maternal inflammation (Kasawara et al, 2016). However, although exercise is well known to reduce systemic inflammation during pregnancy (Tinius, Cahill, Strand, & Cade, 2016), information regarding its influence on human milk markers is scarce or inexistent.…”
Section: Introductionmentioning
confidence: 99%
“… 33 In contrast, daily moderate exercise attenuated systemic inflammation in response to lipopolysaccharide injection in mice. 34 Recently, Aqel, et al 35 demonstrated that daily moderate exercise improves the inflammatory response of LN in NZM2410/J mice through blocking the expression of inflammatory mediators IL-6, tumor necrosis factor-α, CXCL1, and anti-dsDNA antibodies. Their findings also implicated the possibility of adjunct therapeutic strategy for LN.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has been found to be closely linked with thrombotic events during fetal loss as well as fetal distress and indeed, both of the molecular pathways can directly influence the fetal health outcome [ 3 , 4 ]. LPS-induced inflammation during pregnancy has also been shown to increase maternal inflammation as well as thrombosis status [ 5 ].…”
Section: Introductionmentioning
confidence: 99%